2016
DOI: 10.3389/fphar.2016.00486
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological Characterization of the Native Store-Operated Calcium Channels of Cortical Neurons from Embryonic Mouse Brain

Abstract: In the murine brain, the first post-mitotic cortical neurons formed during embryogenesis express store-operated channels (SOCs) sensitive to Pyr3, initially proposed as a blocker of the transient receptor potential channel of C type 3 (TRPC3 channel). However, Pyr3 does not discriminate between Orai and TRPC3 channels, questioning the contribution of TRPC3 in SOCs. This study was undertaken to clarify the molecular identity and the pharmacological profile of native SOCs from E13 cortical neurons. The mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…A subsequent re-admission of external Ca 2+ was followed by an intracellular elevation of Ca 2+ (open circles, Fig. 3A) 9,24 . This entry of Ca 2+ was sensitive to the CRAC channel blocker BTP2 45,46 (1 µM, gray up triangles, Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A subsequent re-admission of external Ca 2+ was followed by an intracellular elevation of Ca 2+ (open circles, Fig. 3A) 9,24 . This entry of Ca 2+ was sensitive to the CRAC channel blocker BTP2 45,46 (1 µM, gray up triangles, Fig.…”
Section: Resultsmentioning
confidence: 93%
“…primary cultures of cortical neurons. Cells were dissociated from cerebral cortices collected from embryonic (E13) mice (with the vaginal plug as E0) according to 9,23,24 . Briefly, tissues were placed in a 1.5 mL Eppendorf tube containing 1 mL of an ice-cold Ca 2+ -and Mg 2+ -free Hank's solution supplemented with 33 mM glucose, 4.2 mM NaHCO 3 , 10 mM HEPES, and 1% penicillin/streptomycin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It could also be suggested that GSK7975A, a well-known antagonist for Orai1 (IC50 = 4 M; [104]), is less effective on Orai2, the dominant isoform expressed in ICC-SM. However, studies on cortical neurons that express only Orai2 showed about 50% block of SOCE by GSK7975A (5 M) [105].…”
Section: Discussionmentioning
confidence: 99%
“…SAR7334 and the tryptoline derivative 8009-5364 are reported to diminish acute hypoxia-induced pulmonary vasoconstriction and pulmonary arterial pressure in isolated mouse lungs [70,71]. SAR7334 has no effect on SOCE in primary cortical neurons [126].…”
Section: Trpc6 Inhibitorsmentioning
confidence: 98%